Etilfosfonato de cobre no manejo da podridão radicular do feijoeiro - Silveira, Gustavo Cesar Dias (2018)
The root rot is an important disease difficult to control in bean and phosphonate can be a alternative. The purpose of this study was to evaluate the effect of a commercial formulation of copper phosphonate in the management of root rot of bean. Two experiments were conducted in central pivot areas planted with Cultivating Pérola (200,000 plants / ha). Copper phosphonate was tested in doses of 1 and 2 L.ha -1 applied only at planting (SP), planting furrow and V1, planting furrow, V1 and 7 days after V1, planting furrow, V1, 7 and 14 days after V1 compared to a control without application. An assessment of the severity of the disease was held at the V4 stage and based on this was calculated the control provided by the treatment. At the end of the tests was determined yield provided by each treatment. The best control treatments were selected and analyzed its effect on the activity of phenylalanine ammonia lyase (PAL), superoxide dismutase (SOD), peroxidase (POX) and polyphenoloxidase (PPO) in greenhouse. A direct in vitro toxicity test was performed in laboratory, using the doses of copper phosphonate in 1 and 2 L.ha -1 , the fungicide bendazol and acibenzolar-S-methyl in 5 strains of the fungus. Statistical analyzes were performed with R 3.1.3 software. In both areas the treatments differed from the control and promoted controls 21-49% and 26-51%. The treatments provided an increase 7-25% of yield. In this way, the best treatment (Copper phosphonate 2 L.ha-1 applied in the planting groove + foliar application in V1, 7 days after V1 and 14 days after V1), which was most highlighted under field conditions, was selected for the accomplishment of the enzymatic and it was observed that this provided increases in POX activity throughout the evaluations. In the direct in vitro toxicity test, the copper phosphonate limited the growth of the fungus. Therefore, it was observed that the copper phosphonate tested was effective in controlling root rot of common bean.